Analysis of Indonesian Public Sentiment towards the Cities of Jakarta, Surabaya and Medan Using the Nave Bayes Algorithm - Rukmana, Andi; Kuswandi, Ferdi; Yanto, Adi (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2024)
The theory of sentiment analysis is interesting to research, this theory aims to group the polarity of a text in a sentence, feature/aspect, or document and then determine whether the opinion contained in the sentence, feature/aspect, or document has positive or negative sentiment. . Sentiment analysis helps in understanding how people respond to certain issues related to these cities (Jakarta, Surabaya, Medan). This research uses the Nave Bayes algorithm by conducting sentiment analysis on cities such as Jakarta, Surabaya and Medan, we can gain valuable insights to support better decision making in various aspects of city development and management. The results of this research provide an accuracy value of 77% for the city of Jakarta, 76% for the city of Surabaya, 75% for the city of Medan. These results also show that the Nave Bayes model has quite good performance in carrying out sentiment analysis.Keywords: Indonesia, Sentimen, Nave Bayes, Twitter